Synthesis of single-crystal perovskite PbCrO3 through a new reaction route at high pressure. Issue 2 (3rd April 2018) - Han, Yunxia; Wang, Shanmin; Liu, Yinjuan; Ma, Dejiang; He, Duanwei; Zhao, Yusheng
ABSTRACT: As a new member in the family of Mott system, perovskite PbCrO3 has recently been uncovered to exhibit fantastic structural transition under pressure, coupled with magnetic, electronic, and ferromagnetic transitions, which provide many opportunities for understanding of correlated system. However, it is still challenging to synthesize high-quality single-crystal PbCrO3, leading to the limited exploration of this Mott compound. In this work, we formulate a new high-pressure reaction route for preparation of high-quality PbCrO3 crystals between PbCl2 and Na2 CrO4 at high pressure of 5–10 GPa and at high temperature of 750–1500°C. Because of the formation of reaction byproduct NaCl, the final product can readily be separated by washing with water. The obtained sample is in the form of single crystal with crystallite size up to 200 μm. In addition, combined with X-ray diffraction measurement, a tentative pressure-temperature synthesis diagram of PbCrO3 is mapped out from the reaction between PbCl2 and Na2 CrO4 and the reaction mechanism is also explored in detail.